Determinants of Intention to Choose Halal Certified Restaurant in West Java - Khomsatun, Nur Kholisoh Kurnia; Priantina, Anita; Rusli, Nurhanani Aflizan Mohamad (Universitas Airlangga, 2024)
The establishment of halal-labeled restaurants that offer a diverse range of food and beverages is in line with the growing awareness of halal certification. However, the importance of halal certification was not fully known by the public. This study aimed to investigate the potential influence of knowledge, attitude, and religiosity on consumers' purchase interest in halal restaurants in West Java. In addition, certain eateries emphasize the natural and cultural aspects of the region. The varied traditional cuisine, business centers, and the presence of Muslim communities make West Java an attractive destination for those seeking a religiously oriented and convenient dining experience. This study used primary data collected from 100 respondents through a questionnaire distributed via Google Forms. The study utilized purposive sampling, a type of non-probability sampling, and employed multiple linear regression analysis using SPSS version 29 for data analysis, the study was conducted in 3 stages, namely t-test, f-test, and coefficient of determination test. The findings indicate that attitude and religiosity factors influence consumer purchase intention at the halal restaurant. Conversely, knowledge was not proven to significantly affect public purchase intention at the halal restaurant in this study. This research has significant implications for halal restaurant owners. Halal restaurant owners in West Java can better understand the needs and preferences of Muslim consumers, strengthen their market position, and promote the growth of the halal industry in the region.